Hoot owl : master of disguise - Taylor, Sean (London : Walker Books, 2015)
A laugh-out-loud page turner from Sean Taylor with wickedly hilarious graphic art from Jean Jullien. Who am I? I am Hoot Owl! Master of Disguise! The darkness of midnight is all around me! But I fly through it like a wolf in the air. Watch out! I am hungry. An here I come!